RESPON PERTUMBUHAN DAN PRODUKSI SAWI HIJAU (Brassica juncea L.) TERHADAP PEMBERIAN JENIS PGPR (Plant Growth Promoting Rhizobacteria) - Aimmatus Sholihah; Mariyatul Qibtiyah; Dian Eka Kusumawati; Emmy Hamidah (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
Brassica juncea L., sometimes known as mustard greens, are annuals with fibrous roots that extend in all directions from the soil surface without producing a crop. Green mustard is one of the most commonly consumed vegetables and is in great demand by the wider community. The amount of mustard produced is not proportional to the high consumption of this vegetable in Indonesia. Therefore, to support sustainable agriculture, efforts need to be made to increase mustard productivity, including the use of microorganisms such as PGPR and environmentally friendly cultivation techniques. The objective of this study was to determine the effect of different types of PGPR on the development and yield of mustard. A standardized Randomized Group Design (RAK) was used in this study. To determine if there were significant differences, the data from the observations were analyzed using the Fisher test (F test at the 5% and 1% levels). Otherwise, the 5% Least Significant Difference test was used. The best results of PGPR types on the growth and production of green mustard plants were obtained in the treatment of PGPR types of Pseudomonas flurescens sp. bacteria compared to other treatments.